A Visual Review and Bibliometric Analysis of Cloud Computing Traffic Flow Forecasting for a Digital Africa - Sello Prince Sekwatlakwatla; Vusumuzi Malele (Latin-American Journal of Computing)
The use of cloud computing has grown globally in recent years. When allocating resources, cloud resources and traffic flow management need to be closely watched and controlled. This paper conducted a bibliographic study based on the Scopus database and the Institute of Electrical and Electronics Engineers (IEEE) to evaluate the adoption rate of resource management and traffic flow forecasting in cloud computing in Africa. There is still uncertainty about cloud computing adoption on the African continent. It is difficult to say that 54 African countries are fully prepared to adopt cloud computing. The growth of internet connectivity and potential economic development in Africa are contributing to cloud computing's rapid growth. Cloud computing enables individuals, private companies, and the government to access computing resources and services remotely. It has the potential to significantly impact the education, healthcare, and economic sectors; however, there are challenges such as limited infrastructure and data security concerns in Africa. This study demonstrates the limitations of the implementation of cloud computing in African countries such as South Africa, Nigeria, Namibia, Botswana, Zimbabwe, Uganda, Kenya, Cameron, Egypt, and Ghana. Only 18.5% of the continent is researching the implementation of cloud computing, and the lack of cloud implementation is a persistent issue because of scarce resources. Africa's adoption of cloud computing can be increased through alternative solutions suggested in the study.